The Effect of Warm Compresses on the Breasts on the Smoothness of Breast Milk Production in Postpartum Mothers at PMB Lismarini Palembang - Devina Anggrainy Dencik (Lembaga Pengembangan Kinerja Dosen, 2024)
Breast milk contains nutritional components and antibodies that are important for the development, immunity and long-term health of babies. However, not all babies get breast milk from their mothers. This can be caused by low breast milk production and irregular breast milk release. Warm compresses are one method of stimulating breast muscles that can increase breast milk production. The type of research used is a quasi-experimental one group pretest posttest. The study population was all postpartum mothers in the PMB Lismarini area with low breast milk production problems. The sampling technique in this study used purposive sampling. Warm compresses were carried out for 7 days with a duration of 10-15 minutes before breastfeeding. The statistical test used was Wilcoxon. The results of the Wilcoxon test showed a p value of 0.003 ≤ 0.05, which means that there is an effect of warm breast compresses on the smoothness of breast milk release. It is expected that health workers will increase educational activities related to the management of irregular breast milk release, one of which is the warm compress method.